Feature Papers in Horticulturae Ⅱ - Archbold, Douglas D. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Horticultural research has been undergoing fundamental changes to improve crop plants as a result of the emergence of new biochemical and molecular techniques. In addition, integration of new technologies with the desire to develop more sustainable production systems has also spurred production level research. The highlighted Feature Papers here reflect the diversity of the types of research performed on horticultural plant species, spanning basic to applied studies, production systems, and postharvest studies, in addition to highlighting some critical issues facing horticultural plant species.